Weight gain pattern in low birth weight infants during first year after kangaroo mother care: a prospective study - Dr. Ashish Satpathy; Dr. Rekha H Udani; Dr. Ruchi Nanavati; Dr. Nanda Kishor Kabra (Pediatric Review: International Journal of Pediatric Research, 2018)
Introduction: Low birth weight infants (LBWI) constitute a worldwide problem with high neonatal and infant mortality and morbidity. Millions of newborn death could be avoided if more resources were invested in proven, low cost interventions designed to address newborn’s needs. Kangaroo Mother Care (KMC) is one such low cost and proven method of care of low birth weight babies but has not yet been widely used in India.In this method the infant is placed between mother’s breasts in direct skin-to-skin contact, gives exclusive breast feeding and are discharged home early.It is particularly useful for care of stable LBW infants below 2000g.Objective: This prospective follow-up study was undertaken and had proved the beneficial effects of KMC to the LBW babies to study “Weight gain in Low Birth Weight infants during first year after Kangaroo Mother Care.Results: KMC reduced mortality, improved breastfeeding rates; KMC for 24 hours was possible with regular intensive counseling of mothers and other family members. The early discharge policy for low birth weight babies was possible and beneficial to achieve intrauterine growth accretion through regular follow-up and monitoring of babies.Conclusion: In low resources setting in developing world like India KMC- reduces mortality, improves breast feeding rate & help in early discharge of low birth weight babies.